The relation between insulin-like growth factor I levels and cognition in healthy elderly: A meta-analysis - Arwert, L.I.; Deijen, J.B.; Drent, M.L. (Growth hormone & IGF research, 2005)
Insulin-like growth factor I (IGF-I) levels and cognitive functioning decrease with aging. Several studies report positive correlations between IGF-I levels and cognitive functioning in healthy elderly. However, because of controversial data no definitive conclusions can be drawn concerning the relation between IGF-I and cognition. Therefore, we carried out a meta-analysis on studies that report on the relation between IGF-I and cognition in healthy elderly. We searched the electronic databases for articles about IGF-I and cognition. Studies from 1985 to January 2005 are included. Two reviewers independently extracted data on study design and cognitive outcomes. Thirteen studies on IGF-I and cognition in elderly, with a total number of 1981 subjects, met the inclusion criteria. On the data from these studies meta-analyses were carried out by means of the program Comprehensive Meta-analysis using a random effects model. Pooled effects show that IGF-I levels in healthy elderly have a positive correlation with cognitive functioning, which appeared to be mainly measured with the mini mental state examination (MMSE). The effect size is 0.6, which indicates the presence of a large positive relationship between IGF and cognition in healthy elderly. These meta-analyses showed an overall relationship between IGF-I levels and cognitive functioning in healthy elderly. Further studies should be performed to clarify the role of IGF-I substitution in preserving cognitive functions with aging.